Carbon Monoxide Poisoning with Neurological, Ocular, and Myocardial Damage: A Case Report - Duc Nguyen; Sinh Nguyen; Anh Lam (Asia Pacific Journal of Medical Toxicology)
Introduction: Carbon monoxide (CO) gas is produced by incomplete combustion of carbon-containing substances. CO has a high affinity with hemoglobin because it reduces oxygen transport causing tissue hypoxia, lactic acidosis, and cell death.Case report: A 32-year-old female patient entered Poison Control Center of Bach Mai Hospital, Ha Noi, Vietnam, because of decreased consciousness, loss of vision in the right eye. Three people sat in a car, the patient sat in the back position, the patient's husband drove, patient's sister sat in the front. They went from Hanoi to Phu Tho province about 50 kilometers with 1.5 hours. 20 minutes after leaving Hanoi, the patient felt headache, dizziness, nausea. Everybody rested in Phu Tho for 45 minutes after returning to Hanoi together, the car ran about 10 minutes, patient felt headache, dizziness, a lot of nausea. The patient's husband felt a terrible headache. Hence, he parked the car on the side of the road and turned off engine but still closed window, all three people lost consciousness one hour later, and they were brought to hospital, at the hospital the right eye of the patient only can see fingers count 1.5 meters, left eye is normal.Discussion: Our hospital didn’t use hyperbaric oxygen therapy so patients could only breathe 100% oxygen through nose. The patient was infused with Solumedrol solution in a high dose. Patient’s HbCO test was 3.8 % after treatment decreasing 1.4%, cardiac enzymes gradually decreased from 78.6 to 15.9 ng/L.Conclusion: After 3 days of monitoring, treatment, the patient recovered her vision and was discharged.